Fiscal dynamics in fragile economies: A VAR analysis of revenue mobilization and government spending in Somalia - Ali, Ali Yassin Sheikh; Nur, Abdulkadir Mohamed (Asian Journal of Economic Modelling, 2025)
This paper aims to analyze the interplay of revenue mobilization and government spending in fragile countries, contrasting the case of Somalia with a focus on fiscal spending, revenue, grants, and tax strategies. The study used quarterly time series data sourced from the Somali Ministry of Finance. Preliminary diagnostic tests, including Augmented Dickey-Fuller (ADF), Phillips-Perron (PP), and KPSS, revealed mixed orders of integration, I(0) and I(1). The cointegration test showed the absence of cointegration, as confirmed by Johansen and bounds tests, justifying the application of the Vector Autoregression (VAR) model in analyzing short-run dynamics and interdependencies. The study found that indirect taxes serve as a key component of revenue generation, exhibiting a stable relationship with government spending. It also found that grants significantly affect government spending, indicating the dependency of fiscal operations on external support. Additionally, there is a strong, significant positive association between total revenue and government spending, highlighting the need for appropriate fiscal policy. Policy recommendations include strengthening tax administration and anti-corruption measures. Furthermore, reforms should focus on modernizing tax systems through digital initiatives and governance reforms, improving indirect taxes for greater coverage, and diversifying revenues to reduce dependency on external assistance.